Estudo farmacobotânico de seis espécies de uso medicinal no nordeste brasileiro. - Malheiros, Sarah Guimarães de Lima (2012)
Medicinal plant is any plant that has, in one or more organs, substances that can be used for therapeutic purposes or which are precursor of semi-synthetic drugs. Natural products and their derivatives represent more than 50% of all drugs in clinical use worldwide, being higher plants supplying at least 25% of the total. Although the growing use of medicinal plants has been very large in recent decades, there is still a significant lack of research data in this area, especially with regard to quality control of herbal drugs. This work aimed the pharmacobotanical study of six angiosperms medicinal species commonly used in northeastern Brazil, in order to support the quality control of their herbal drugs, since the morphological and anatomical data for these species are scarce, although the pharmacological importance of each is well-defined. For this purpose, we performed morphological and anatomical studies of roots, stems and leaves and ultra-structural study of leaves surfaces of Ageratum conyzoides, Justicia pectoralis, Cnidoscolus urens, Cnidoscolus infestus, Aristolochia papillaris e Aristolochia birostris. The results showed, especially the anatomical data, such as contour epidermal cell wall, types of stomata, trichome type and distribution and organization of vascular bundles, showed particular and distinctive characters of each species. The morphoanatomic analysis of the species in study allowed the characterization of each one, providing basis for their correct identification and distinction of closely related and morphologically similar species.